2022
DOI: 10.1039/d2gc01840c
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of plastic waste into high-value lubricants: techno-economic analysis and life cycle assessment

Abstract: The conversion of plastic waste into high-quality lubricants is more profitable than sorting the waste or converting it into liquid fuels. A life cycle assessment showed that the emissions were lower than those of petroleum lubricants of similar quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…[18][19][20][21] Recent efforts to model a conceptual pilot plant for this process have shown that Pt/STO upcycling at a scale of 250 Mt day −1 could protably generate lubricant materials while reducing process emissions relative to current industrial methods. 22 These results incentivize further study of Pt/STO upcycling, part of which involves scale-up of Pt/STO catalyst synthesis to the kilogram and ton scales. STO nanocuboids have also previously been investigated as a model catalyst support, and as a bridge between templates for surface science studies and performance-oriented, high surface area supports, and the work developed here may also affect innovation of other M/STO catalyzed processes.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Recent efforts to model a conceptual pilot plant for this process have shown that Pt/STO upcycling at a scale of 250 Mt day −1 could protably generate lubricant materials while reducing process emissions relative to current industrial methods. 22 These results incentivize further study of Pt/STO upcycling, part of which involves scale-up of Pt/STO catalyst synthesis to the kilogram and ton scales. STO nanocuboids have also previously been investigated as a model catalyst support, and as a bridge between templates for surface science studies and performance-oriented, high surface area supports, and the work developed here may also affect innovation of other M/STO catalyzed processes.…”
Section: Introductionmentioning
confidence: 99%
“…44 These calculations demonstrated that this hydrogenolysis process is a promising plastic upcycling technology with reduced CO 2 emissions. 44…”
Section: Hydrogenolysis Of Polyolefins With External Hydrogenmentioning
confidence: 89%
“…Pt- and Ru-based catalysts are predominantly used in the hydrogenolysis of polyolefins. 40–47 The supports used are usually non-acidic materials, such as carbon materials, 40,48–51 CeO 2 , 52–54 TiO 2 , 55,56 SrTiO 3 , 47 ZrO 2 (ref. 53) and so on.…”
Section: Catalytic Hydroconversion Processes For Deconstruction Of Po...mentioning
confidence: 99%
See 2 more Smart Citations